Long-Term Radiographic Changes in Stemless Press-Fit Total Shoulder Arthroplasty - Beck, Sascha; Patsalis, Theodor; Busch, André; Dittrich, Florian; Wegner, Alexander; Landgraeber, Stefan; Jäger, Marcus (Zeitschrift für Orthopädie und Unfallchirurgie, 2020)
Introduction Stemmed humeral implants have represented the gold standard in total shoulder arthroplasty (TSA) for decades. Like many other joints, the latest trends in TSA designs aim at bone preservation. Current studies have demonstrated that native proximal humeral bone stresses are most closely mimicked by stemless implants. Nevertheless, there are concerns about the long-term performance of stemless designs. The aim of the present study was to evaluate the long-term radiographic changes at the proximal humerus in anatomical stemless press-fit TSA.Materials and Methods Between 2008 and 2010, 48 shoulders in 43 patients were resurfaced using an anatomic stemless shoulder prosthesis (TESS, Biomet). Thirty shoulders in twenty-five patients who were aged 65.7 ± 9.9 (34 to 82) years were available for clinical and radiographic review at a mean follow-up of 94.0 ± 8.9 (78 to 110) months.Results Radiographic changes of the proximal humerus due to stress shielding were found in 38.4% of the stemless TESS implants. Mild stress shielding accounted for 80% of the observed radiographic changes. Radiographs exhibited stable fixation of the stemless humeral press-fit implant at early and late follow-up. In contrast, radiolucent lines at the glenoid implant were found in 96.1% of the cases. Irrespective of the degree of radiographic changes, clinical scores (VAS, Quick-DASH, Constant score) significantly improved at follow-up.Conclusions The anatomic stemless press-fit implant seems to be favorable in terms of implant-related stress shielding. Clinical outcome was not affected by radiographic changes, demonstrating an 8-year clinical performance that seems to be comparable to conventional stemmed TSA.
Keywords: stemless; press-fit; shoulder arthroplasty; stress shielding; radiographic changes; long-term follow-up